Сверхширокополосная антенна для радиомониторинга - Воргуль, А. В.; Лучанинов, А. И.; Лихограй, В. Г.; Назаренко, В. А.; Щербина, А. В. (ХНУРЕ, 2019)
A design of an axial symmetric UWB antenna in the form of a rotation body with a generatrix of complex shape in the frequency range of 1–7 GHz are considered for radio monitoring tasks. Using the FEKO software, a search of optimal generatrix shape of the UWB antenna to provide the required broadband was made. A genetic algorithm is used for the optimization process. It is shown that the choice of optimization criterion allows to design an UWB antenna which is being meeting the specified requirements in the operating frequency band.
Keywords: радиомониторинг; UWB antenna